Teacher’s Performance in Improving Student Learning Outcomes at SDN 75 Bentang - Alauddin Alauddin; Nursalam Nursalam; Muh Basri (Universitas Muhammadiyah Enrekang, 2022)
This study aimed to determine the teachers' performance in improving student learning outcomes at SDN 75 Bentang and the inhibiting and supporting factors to improve the teachers' performance. This research method used a qualitative descriptive approach, meaning that the data collected was based on the actual conditions. The aim was to find real data directly with actual conditions. The results obtained from this study indicated that the description of teachers' performance was seen from a) educating, b) teaching, c) training, d) guiding, e) assessing and evaluating, and schools in improving the performance of educators, namely by making several efforts so that the goal of the achievement was successful. Such as by making efforts to establish good relationships with other educators and providing facilities and infrastructure based on the needs of educators. Evaluating and supervising the performance of educators directly, namely before and after carrying out the teaching and learning process. However, there were still several inhibiting and supporting factors. The inhibiting factor was the number of teachers with civil servant status was insufficient. Because some of the teachers were relatives, some tasks were managed properly between school assignments and outside of the school. The supporting factors in improving teachers' performance at SD Negeri 75 Bentang were the high sense of togetherness and kinship that existed in the school environment, the high willingness to learn from the educators and the high commitment of the principal to improving the performance of teachers at SD Negeri 75 Bentang.